Strategic Human Resources Management: A Study of the Alignment of HR Practices with Overall Business Strategy and Its Impact on the Organization Based on Occupational Psychology Principles - Kashoob, Said Salim Mohad; Al-Khazaleh, Shadi Said; Alwreikat, Eman Ibrahim; Alzubaidi , Rania; Beshr, Baligh Ali Hasan; Darawsheh, Saddam Rateb (Journal of Posthumanism, 2025)
HR systems have the potential to confer a lasting competitive edge by enabling the development of firm-specific capabilities. The strategic management of human resources involves aligning the overarching strategic goals of the organization with HR strategy and performance. Grounded in Industrial and Organizational Psychology principles, this research examines how psychological factors influence HR practices and organizational effectiveness. Utilizing a survey approach, standardized autonomous questionnaires were distributed to 50 executives and collected from 29 managers. The study revealed no notable disparities in HRM effects based on work arrangements. However, years of experience significantly influenced HRM dynamics and performance indicators, underscoring its pivotal role in shaping employee behavior, motivation, and job satisfaction—key elements in Occupational Psychology. In summary, expertise wielded a more profound influence than work arrangements on HRM-related outcomes. This study contributes significantly to the reservoir of knowledge in both academic and practical realms, integrating psychological insights into HRM strategies. It offers substantial recommendations to enhance HRM and SHRM management, ultimately bolstering the organization’s overall success by leveraging psychological principles to optimize workforce performance and well-being.